spectroscopic stury of lewis bases coordinating to vanady - Baghdad Science Journal (مجلة بغداد للعلوم)
formation constants for the conrdination of aniline pyridine dimethyl sulfoxide dimethyl formamide ethanol dimethylamine have been determined the cordination